2018
DOI: 10.1111/clr.13292
|View full text |Cite
|
Sign up to set email alerts
|

Reposition of the bone plate over the antrostomy in maxillary sinus augmentation: A histomorphometric study in rabbits

Abstract: The bone healing in the elevated sinus space was similar irrespective of the coverage of the antrostomy. After 8 weeks, the bone plate repositioned on the antrostomy was incorporated while at the control sites the healing was still incomplete. Residual defects were still present in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
54
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(69 citation statements)
references
References 43 publications
11
54
2
Order By: Relevance
“…Surgical trauma and the formation of a regenerative compartment between the bone walls and the Schneiderian membrane result in a spontaneous bone apposition in the maxillary sinus. However different studies have shown that bone is forming from the denudated bone walls of the sinus while the sinus mucosa did not show evident signs of bone formation [24,25,26,27]. In fact, in the present study, the healing of the augmented sinus was also achieved in the group that used cortical lamina so that the partial exclusion of the sinus mucosa from the healing bone process seems not to have affected the results.…”
Section: Discussionmentioning
confidence: 42%
“…Surgical trauma and the formation of a regenerative compartment between the bone walls and the Schneiderian membrane result in a spontaneous bone apposition in the maxillary sinus. However different studies have shown that bone is forming from the denudated bone walls of the sinus while the sinus mucosa did not show evident signs of bone formation [24,25,26,27]. In fact, in the present study, the healing of the augmented sinus was also achieved in the group that used cortical lamina so that the partial exclusion of the sinus mucosa from the healing bone process seems not to have affected the results.…”
Section: Discussionmentioning
confidence: 42%
“…To prevent the movement of the bony plate and to gain adequate stability, cyanoacrylate has been suggested to glue the plate to the bony edges of the antrostomy [17]. Cyanoacrylates (as methyl 2-cyanoacrylate or ethyl 2cyanoacrylate) are widely used in surgery and have shown good compatibility [18] and biomechanical strength for fixation of grafts [19].…”
Section: Introductionmentioning
confidence: 99%
“…A statistically significant difference (p = 0.018) was instead found in the close-to-window regions in which new bone was found in proportions of 25.8% and 17.6% in the treated and untreated sites, respectively. Aiming to improve the healing at both the elevated space and the antrostomy, precluding the ingrowth of connective tissue within the elevated region, the reposition of the bone window, removed after the osteotomy, has been proposed both in clinical [13,14] and experimental studies [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…More new bone was found within the sinus covered with the repositioned bone window, formed in contact with its inner surface. In another study in rabbits [16], a similar experimental design was applied. Deproteinized bovine bone mineral was used as filler material in both sites, and the repositioned bone window was fixed with cyanoacrylate glue in the test group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation